Title Page Evolution of the “Modernization” Definition In Modern China - Serikkaliyeva, A E (Farabi Journal of Social Sciences, 2016)
Chinese model of modernization was analyzed at the large number of papers, but Chinese conception and understanding of this term seems different from the global or international representation. In this article several definitions of the “modernization” term are considered. Also, classical, European and Chinese understanding of the modernization conception are compared.